Attitudes in patients with diabetes mellitus type 1 and type 2 - Oleg Gennad'evich Motovilin; Olga Vital'evna Lunyakina; Elena Viktorovna Surkova; Yulia Andreevna Shishkova; Olga Georgievna Mel'nikova; Alexander Yur'evich Mayorov (Сахарный диабет, 2012)
Aims. To compare disease attitudes in patients with type 1 and type 2 diabetes mellitus (T1DM and T2DM) and to evaluate relationship between attitudes and psychological welfare of these groups. Materials and Methods. We examined 140 patients with T1DM and 70 patients with T2DM on insulin therapy (mean age 22.6?3.2 and 60.1?7.8 years; male/female ratio 47/93 and 15/55; duration of diabetes 12.1?5.7 and 11.4?6.5 years, HbA1c 9.3?2.2 и 9.0?1.4%, respectively). Psychological parameters were assessed by following methods: Bekhterev Disease Attitude Typing (DAT), Colour Attitude Test (CAT), SF-36 (36-Item Short Form Health Survey), Spielberger Anxiety Inventory (SAI), CES-D Depression Scale, Dembo-Rubinstein (DR) technique for self-esteem assessment. Results. DAT showed increased sensitive attitude to their disease in patients with T1 and T2DM, being significantly higher in T2DM. According to CAT, T2DM patients perceive DM as a disease, associated with severe manifestations and complications, while T1DM patients tend to incorporate the notion of diabetes with lifestyle. Cluster analysis showed negative disease attitude to be associated independently of diabetes type with decrease in quality of life and emotional deterioration (higher anxiety and depression score, as measured by SF-36, SAI and CES-D). Conclusion. Disease attitude typing and correction is important in management of DM. Emotional acceptance allows improvement in quality of life and promotes psychological welfare. Also, despite the absence of direct relationship between HbA1c and disease attitudes (which, is plausibly non-linear), emotional acceptance may favour glycemic compensation due to increase in compliance.